Individual duty - Van Blarcom, Sam L. (My University, 1891)
Introduction: The present age may be justly termed the age of combines. Every interest, every industry, every corporation and institution unite with every other for aid and protection. Capital is combined against labor, and labor is organized to protect itself from the attacks of capital. The people organize to attack the corporations, and the corporations organize to counteract the efforts of the people. Employers combine to reduce, and employees combine to enhance the value of labor. It is evident that under such a condition of affairs the freedom of an individual is greatly limited, the range of his choice and responsibilities is greatly narrowed, and the force by which high character is developed is materially weakened. The effect of such a system of combinations is to cause a constant war between labor and capital, and a continual strife between employer and employee.
Individual rights
Citation: Van Blarcom, Sam L. Individual duty. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Labor; Corporation; Capitalism; I/O; Demand; Theses; Manuscripts (documents)